Assessment Penerapan Strategi Pembelajaran di SMP Islam Desa Darek - Khairun Najah (Syntax Corporation Indonesia, 2024)
Determining learning strategies in schools is a very important thing for teachers to do so that learning objectives can be achieved optimally. The learning strategy is an attempt to convey knowledge to students. Because the realization of good learning cannot be separated from how to design learning strategies. So that it can guide students to achieve an understanding of the material presented. This study aims to find out the description of the assessment of learning strategies applied in Darek village Islamic middle school, to find out the description of the implementation of learning strategies in Darek village Islamic Middle school whether it is in accordance with the needs and abilities of students, to find out the efforts of teachers and educators when getting students who have low abilities in learning. The method used in this research is qualitative. The data collection technique in this study was by interviewing teachers at the school. The results of the study show that the implementation of the learning strategies that have been implemented are in accordance with the needs and abilities of students, than there are two learning strategies that have been implemented, namely: 1) the strategy of the expository learning model (lecture model), in which the teacher gives material to students using the lecture model and then proceeds with a question and answer system or discussion. 2) Cooperative learning model strategy, the teacher forms small groups so that students can work together in teams, and the learning outcomes can be presented in front of the class. Teachers also provide special guidance to students who have low abilities in learning.